Fiber growth of goats as influenced by the doe's genotype, plane of nutrition and physiological stage (gestation and lactation) - Casey, N.H. (Norman Henry) (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Animal Production))--University of Pretoria, 2006.